2018
DOI: 10.1177/0269881118788806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega-3 fatty acid supplementation on cigarette craving and oxidative stress index in heavy-smoker males: A double-blind, randomized, placebo-controlled clinical trial

Abstract: This study showed that high-dose omega-3 fatty acid supplementation appears to be useful in reducing cigarette craving and oxidative stress index in heavy-smoker males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The nicotine dependence severity was measured by Fagerström Test for Nicotine Dependence (FTND), 21 and peak‐year was defined as years of smoking × cigarettes smoked per day/20. The inclusion criteria for smokers were as follows: (1) smoking at least 1 daily for >2 year; (2) smokers had no period of smoking abstinence and no attempt to quit; (3) FTND > 4 and smoking at least 20 cigarettes per day were defined heavy smokers, and vice versa as light smokers 9,22 . The nonsmokers were included as those who smoked less than five cigarettes in their lifetime.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nicotine dependence severity was measured by Fagerström Test for Nicotine Dependence (FTND), 21 and peak‐year was defined as years of smoking × cigarettes smoked per day/20. The inclusion criteria for smokers were as follows: (1) smoking at least 1 daily for >2 year; (2) smokers had no period of smoking abstinence and no attempt to quit; (3) FTND > 4 and smoking at least 20 cigarettes per day were defined heavy smokers, and vice versa as light smokers 9,22 . The nonsmokers were included as those who smoked less than five cigarettes in their lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…(2) smokers had no period of smoking abstinence and no attempt to quit; (3) FTND > 4 and smoking at least 20 cigarettes per day were defined heavy smokers, and vice versa as light smokers. 9,22 The nonsmokers were included as those who smoked less than five cigarettes in their lifetime. Exclusion criteria for both groups were (1) any physical illness such as obstructive lung disease, epilepsy, brain tumour, cerebrovascular disease, or hepatitis; (2) urine test suggesting other substance or drug abuse (except nicotine); (3) existence of a neuropsychiatric disease; or (4) claustrophobia and other contraindications to magnetic resonance imaging.…”
Section: Participantsmentioning
confidence: 99%
“…As smoking-induced oxidative stress is thought to contribute to lower levels of omega-3 fatty acids in plasma, Sadeghi-Ardekani et al evaluated the effects of omega-3 fatty acid supplementation on oxidative stress index in heavy-smoker males. They found that high-dose of omega-3 fatty acid supplements (180 mg of eicosapentaenoic acid and 120 mg of docosahexaenoic acid) for three months decrease total oxidant status and oxidative stress index [214].…”
Section: Smokementioning
confidence: 99%
“…As CSinduced oxidative stress is thought to lower levels of plasma omega-3 fatty acids, a study evaluated the effects of omega-3 fatty acid supplementation on oxidative stress in heavy-smoker males, showing that high dose of omega-3 fatty acid supplements for 3 months decreases oxidative stress index (i.e. total oxidant status/total antioxidant capacity) (144) .…”
Section: Antioxidant Supplementation In Smokersmentioning
confidence: 99%